BREEDING AND GENETIC RESEARCH OF SOFT WHEAT (Experimental biology, 2016)
Obtained highly productivity, resistance to leaf rust and good quality grain isogenic lines IL-Hg, IL-BgHg and IL-Pc. Indicators of spike productivity and weight of 1000 grains of line IL-Hg was significantly higher than those of control variety. Wild species as the parent component favorably affect a high percentage of tying grains. Genome of “Nadezhda” variety is highly compatible with genomes wild species compared with other varieties of wheat. Hybrids obtained by crossing t.timopheevi with soft wheat have heteroplasmic state: simultaneously present copies of wild and wheat typies. Obtained modified plants on a number of qualitative and quantitative traits under the action of a chemical compound - CdCl2 on varieties of soft wheat. Genetic analysis carried out on the basis of reciprocal crosses showed that modified traits of mutants are inherited independently of direction of crossing.
Keywords: mutagenesis; isogenic lines; substitution of chromosomes of wheat; selection; distant hybridization; variety.